2013
DOI: 10.1021/jm301654b
|View full text |Cite
|
Sign up to set email alerts
|

N-Cinnamoylated Chloroquine Analogues as Dual-Stage Antimalarial Leads

Abstract: The control of malaria is challenged by drug resistance, and new antimalarial drugs are needed. New drug discovery efforts include consideration of hybrid compounds as potential multitarget antimalarials. Previous work from our group has demonstrated that hybrid structures resulting from cinnamic acid conjugation with heterocyclic moieties from well-known antimalarials present improved antimalarial activity. Now, we report the synthesis and SAR analysis of an expanded series of cinnamic acid derivatives displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
81
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 32 publications
(71 reference statements)
2
81
0
1
Order By: Relevance
“…189b, 194 As already mentioned in the previous section, it was found that the compounds with the dipeptide spacer (170) inhibited in vitro both hemozoin formation and development of blood-stage P. falciparum, while compounds without the spacer (171) were better falcipain-2 (FP2) inhibitors; none of the compounds was a falcipain-3 (FP3) inhibitor. In order to obtain additional knowledge about the FP2 inhibitory capacity of the latter compounds, molecular docking and MD simulations were performed to predict the structures of the complexes between the compounds with or without the dipeptide linker and FP2 (PDB code: 3BPF) or FP3 (PDB code: 3BWK).…”
Section: Aiming At Inhibition Of Other Parasitic Targetsmentioning
confidence: 74%
See 2 more Smart Citations
“…189b, 194 As already mentioned in the previous section, it was found that the compounds with the dipeptide spacer (170) inhibited in vitro both hemozoin formation and development of blood-stage P. falciparum, while compounds without the spacer (171) were better falcipain-2 (FP2) inhibitors; none of the compounds was a falcipain-3 (FP3) inhibitor. In order to obtain additional knowledge about the FP2 inhibitory capacity of the latter compounds, molecular docking and MD simulations were performed to predict the structures of the complexes between the compounds with or without the dipeptide linker and FP2 (PDB code: 3BPF) or FP3 (PDB code: 3BWK).…”
Section: Aiming At Inhibition Of Other Parasitic Targetsmentioning
confidence: 74%
“…In the case of FP2, the shorter distance between the vinyl bond of the compounds without the linker and the Cys thiolate of the enzyme than for the compounds with the spacer is in line with the experimental observation that the former were better FP2 inhibitors. 194 While molecular docking combined with realistic molecular models is able to provide static information about the most favorable host−guest configurations, MD simulations can be used to gain knowledge on the evolution of the docked configurations with time. In fact, Gomes and co-workers showed that FP2 inhibitory activities measured experimentally could be correlated with the time evolution of the distance between the vinyl bond and the enzyme's Cys thiolate determined from classical MD simulation.…”
Section: Aiming At Inhibition Of Other Parasitic Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 4-10 were prepared following a straightforward low-cost synthetic pathway, previously reported, and the analytical and structural data were in agreement with formerly published data. 13,14 Compounds' antiproliferative properties against MKN-28 (gastric cancer), Caco-2 (colorectal adenocarcinoma), MCF-7 (breast cancer) and HFF-1 (human foreskin fibroblasts) cell lines were determined according to the National Cancer Institute (NCI, USA) procedure, which uses the protein-binding dye sulforhodamine B.…”
mentioning
confidence: 99%
“…To respond to those needs, we have tested the activity of cinnamic acid conjugates of the 8-aminoquinoline primaquine (PQ) and the 4-aminoquinoline chloroquine (CQ) against L. infantum. The rationale for these tests was that (i) these conjugates have been recently reported as interesting antimalarial leads (8)(9)(10) and (ii) PQ (compound 1) and CQ (compound 3) have proven activity against several protozoans, including visceralizing Leishmania (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%